Body physique and dominant somatotype in elite and low-profile athletes with different specializations. - Gutnik, B.; Zuoza, A.; Zuoziene, I.; Alekrinskis, A.; Nash, D.; Scherbina, S. (Medicina, 2015)
Anthropometric indices, Anthropometry, Athletes, Morphology, Somatotype Somatotyping is helpful in sports in which the body shape could influence the resulting performance. The purpose of this study was to determine the somatotype of high profile Lithuanian athletes in kayaking, basketball and football and to compare between disciplines and with low level sportsmen of the same age. A total of 72 young male sportsmen aged from 18 to 24 years were divided into three groups (kayakers, basketball and football players). Each group contained almost equal numbers of low level and elite, international level sportsmen. Anthropometric measurements of the players were used to establish somatotypes. The greatest difference was observed in the mesomorphic component of elite kayakers compared to the low profile sportsmen. Mesomorphy could also be used to predict sport ability. The range of mesomorphy for elite footballers was from 0 to 4.6, for basketball players from 4.6 to 5.9, and for kayaking, from 5.9 and higher. Individual groups of elite sportsmen displayed different modes of somatotype. The kayakers were predominantly endomorphic; the basketball players mostly endomorphic and the footballers most often ectomorphic. No distinguishable patterns of somatotype were displayed by the low level sportsmen. Morphometric characteristics of the athlete`s body and the fractional somatotype can be used as guiders and markers of the chosen sport and method of training. The results emphasize the necessity for a specific somatotype to reach a high profile in the selected area of sport and thus support morphometric oriented studies. Further studies could elucidate differentiation by age and sex.